Copresence With Virtual Humans in Mixed Reality: The Impact of Contextual Responsiveness on Social Perceptions - Pimentel, Daniel; Vinkers, Charlotte (Frontiers in Robotics and AI, 2021)
Virtual humans (VH) - automated, three-dimensional agents - can serve as realistic embodiments for social interactions with human users. Extant literature suggests that a user’s cognitive and affective responses towards a VH depend on the extent to which the interaction elicits a sense of copresence, or the subjective “sense of being together”. Furthermore, prior research has linked copresence to important social outcomes (e.g., likeability, trust), emphasizing the need to understand which factors contribute to this psychological state. Although there is some understanding of the determinants of copresence in Virtual Reality (VR) (cf. Oh et al., 2018), it is less known what determines copresence in Mixed Reality (MR), a modality wherein VHs have unique access to social cues in a ‘real world’ setting. In the current study, we examined the extent to which a VH’s responsiveness to events occurring in the user’s physical environment increased a sense of copresence and heightened affective connections to the VH. Participants (N = 65) engaged in two collaborative tasks with a (non-speaking) VH using a MR headset. In the first task, no event in the participant’s physical environment would occur, which served as the control condition. In the second task, an event in the participants’ physical environment occurred, to which the VH either responded or ignored depending on the experimental condition. Copresence and interpersonal evaluations of the VHs were measured after each collaborative task via self-reported measures. Results show that when the VH responded to the physical event, participants experienced a significant stronger sense of copresence than when the VH did not respond. However, responsiveness did not elicit more positive evaluations towards the VH (likeability, emotional connectedness). This study is an integral first step in establishing how and when affective and cognitive components of evaluations during social interactions diverge. Importantly, findings suggest that feeling copresence with VH in MR is partially determined by the VH’ response to events in the actual physical environment shared by both interactants.